Amel Dunqil’s Poem, “Spartacus’s Last Words: A Stylistic Study - Nael Abdulhussen Abdulsaed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Amal Dunqil is a rebelling poet against the society state of affairs, and that is very clear in his poetry; so he was seen, by a few critics as a leftist poet. This is because of his political opposition to despotism and his refusal of peace treaty with Israel. This attitude is reflected in his well-known poem “Don’t Make Peace”, which came to be an icon in Arabic countries. His opponents assume that his poetry is direct, others say that he has a rural mind that looks for revenge along with other things imputed to him. This research aims at showing the textual mechanisms that Dunqil uses in his text, revealing the levels of the text according to a stylistic study of “The Last Words of Spartacus”. The research depends on stylistics as an application to read the text for it can disclose the textual points of creativity and splendour. The study consists of two parts: the first is theoretical concerned with introducing the meaning of stylistics and showing its old relation to discourse, in addition to the oldness of the strategy and mechanisms of stylistics. Therefore, the researcher dispensed with a theoretical introduction. The second part is a textual application on stylistics adopting the text as a subject, and therefore, the researcher depended only on the collection of poems as a resource as a way to maintain dealing only with the text. The research is a cognitive attempt that accepts being correct or mistaken.